The adaptation of English loanwords in ChiNdau - Chinheya, Moreblessing (Rhodes University, 2026)
This study explores the extent to which ChiNdau has borrowed from English and examines the adaptations of these loanwords. The objective was to find out the extent to which ChiNdau have borrowed from English and to establish the kind of modifications which the loanwords have undergone and the impact borrowing has had on indigenous ChiNdau words. The study utilized data from five text-based sources, the ChiNdau Dictionary, Vemuganga Community Radio Facebook page, ChiNdau Bible, Rekete ChiNdau Facebook page, and ChiNdau Hymn Book. The findings reveal an abundance of English loanwords in ChiNdau which suggests that English has had a significant impact on the development of modern ChiNdau. The study found that nouns constituted the majority of borrowings, surpassing verbs in frequency. It was also found that cultural borrowings dominated, reflecting the influence of modernity, technology, and religion on the ChiNdau lexicon. Phonological adaptations were prominent, as the findings also showed that ChiNdau exhibits distinct phonological systems, which necessitate modifications when English words are borrowed into ChiNdau. Furthermore, the findings also indicated that the loanwords underwent a number of morphological modifications. Drawing on insights from the Matrix Language Frame (MLF) model (Myers-Scotton 1993b) the study found that the donor language (English) contributed Content Morphemes, while the host language (ChiNdau) supplied System Morphemes to ensure that the borrowed words conform to its grammatical structure. These adaptations included the attachment of noun class prefixes to English stems, and the attachment of various grammatical affixes to English verb stems. Due to the limited scope of the study, short data collection period and lack of spoken data it was not possible to establish the impact which the English loanwords have made on indigenous chiNdau words. However, the findings of the study suggest that there are opportunities for future research to explore broader contexts and long-term borrowing trends.
Keywords: Ndau language (http://id.loc.gov/authorities/subjects/sh85024233); English language--Influence on foreign languages (http://id.loc.gov/authorities/subjects/sh85043592); Code switching (Linguistics) (http://id.loc.gov/authorities/subjects/sh85027647); Linguistic borrowing (https://www.wikidata.org/wiki/Q1345001)